Computational modeling of lumbar disc degeneration before and after spinal fusion. (December 2021) - Godinho, M.I.; Carvalho, V.; Matos, M.T.; Fernandes, P.R.; Castro, A.P.G.
Abstract: Background: Advancing age and degeneration frequently lead to low back pain, which is the most prevalent musculoskeletal disorder worldwide. Degenerative changes in intervertebral discs and musculo-ligamentous incapacity to compensate sagittal imbalance are typically amongst the sources of instability, with spinal fusion techniques being the main treatment options to relieve pain. The aims of this work were to: (i) assess the link between ligament degeneration and spinal instability by determining the role of each ligament per movement, (ii) evaluate the impact of disc height reduction in degenerative changes, and (iii) unveil the most advantageous type of posterior fixation in Oblique Lumbar Interbody Fusion to prevent adjacent disc degeneration. Methods: Two L3-L5 finite element models were developed, being the first in healthy condition and the second having reduced L4-L5 height. Different degrees of degeneration were tested, combined with different fixation configurations for Oblique Lumbar Interbody Fusion. Findings: Facet capsular ligament and anterior longitudinal ligament were the most influential ligaments for spinal stability, particularly with increasing degeneration and disc height reduction. Pre-existent degeneration had lower influence than the fusion procedure for the risk of adjacent disc degeneration, being the highest stability and minimal degeneration achieved with bilateral fixation. Right unilateral fixation was more suited to reduce disc stress than left unilateral fixation. Interpretation: Bilateral fixation is the best option to stabilize the spinal segment, but unilateral right fixation may suffice. This has direct implications for clinical practice, and the extension to a population-based study will allow for more efficient fusion surgeries. Highlights: The effects of spinal fusion were studied with a finite element model. It was found that ligament degeneration follows the evolution of disc degeneration. Spinal fusion is due to contribute to adjacent disc degeneration. Bilateral fixation is the best option, but unilateral right fixation may be enough.